APLIKASI MONITORING PRESENTASE PERSEMBAHAN JEMAAT GEREJA BATAK KARO PROTESTAN (GBKP) BERBASIS ANDTOID - Heliyani Welbri Br Sitepu; Bersama Sinuraya (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2020)
Monitoring Batak Karo Protestant Chruch (GBKP) cruch offerings is a routine process of collecting data offerings and measuring progress on program objectives. Monitori change, which focus on processes and outputs. Monitoring provides basic data to answer problems. In monitor this presentation the data collection includes offerings from the dungung to the modern. But the process of distributing presentations is still manual, so it takes time to the distribute to the moderamen. Based on this, an aplication for the persentage distribution of Android-based Protestant Batak Karo Chruch congregation was built.Keywords: Registration, Android, Simulation